Grooming Child Literature Review: Analisis Kasus Grooming Child pada Penggunaan Media Sosial: Analisis Kasus Grooming Child - Ika yuniartiningtiyas Ika; Slamet Widodo (LPPM Press, 2022)
Grooming Child is one of the bad actions from adults towards children that can provoke violence to sexual harassment. As is known, that the world is currently entering the 4.0 era where all activities can be facilitated by using machine access, such as a car or motorbike as a vehicle or mobile phone media as a means of communication between one another. Grooming Child can occur through digital access. One application that is used to approach small children is through a game application or game. From several cases, there are still many incidents of Grooming Child that have not been handled by law enforcement officers, as is the case in Malang City. Police as one of the law enforcement officers, which do more preventive efforts than repressive handling. Although this case is very dangerous for the future and survival of children, the incidence of sexual crimes through social media is still common and the trend is increasing. Therefore, efforts to overcome this must involve many elements of society, especially parents, who must be wise in supervising the use of social media so as not to get caught up in sexual crimes commonly known as Grooming Child.